Issues of implementation of marketing activities in the economy in the development of small and private enterprises in the global economy - R.N Zhiamuratov (Proceedings of The ICECRS, 2020)
This paper investigates major points of the issues of implementation of marketing activities in the economy in the development of small and private enterprises in the global economy. On this case, research has pointed in both methodological and theoretical basis of the issue. Moreover, research has been investigated with the development of the development of small and private enterprises in the global economy with outcomes and shortcomings as the whole.